Panorama da COVID-19 no Estado do Pará - CAMPOS, Giovanny Patrick Brito (2022)
The first official case of Covid-19 in the state of Pará, Brazil, was registered in Belém City on March 18, 2020. The Geographic Observatory of COVID-19 in the state of Pará was one of the groups that studied the evolution of the pandemic. As a product of the activities of this group, the present study analyzed the space-time evolution of the Covid-19 pandemic in Pará, between March 2020 and April 2021. On the regional (states, geographical regions - RGINT) and local (municipalities) scale, a systematization and mapping of the disease records obtained from Fiocruz, The State Department of Health of Pará (Sespa), Brasil.IO, and the municipal authorities (epidemiological bulletins) were carried out. The results confirmed the occurrence of two peaks or "waves" of cases and deaths. The first "wave" of the disease in 2020 spread, mainly from Belém, and the second, from 2021, from the municipalities of Baixo Amazonas. Among the spatial factors analyzed, the most relevant was the relationship between COVID-19's progress with the urban network and demographics. The analysis did not account for the more local realities of the pandemic, and certainly the data review can lead to more or less marked modification of the curves.